2017
DOI: 10.1016/j.jinorgbio.2016.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of antibiotic-activity through complexation with metal ions - Combined ITC, NMR, enzymatic and biological studies

Abstract: Enhancement of antibiotic-activity through complexation with metal ionsCombined ITC, NMR, enzymatic and biological studies,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 37 publications
0
37
0
1
Order By: Relevance
“…The concentration dependence of the PenNa chemical shifts using DMSO-d 6 solvent: The concentration dependence of the geminal proton resonances in D 2 O has been previously reported [22]. Herein we report our study for the dimethylsulfoxide solvent.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…The concentration dependence of the PenNa chemical shifts using DMSO-d 6 solvent: The concentration dependence of the geminal proton resonances in D 2 O has been previously reported [22]. Herein we report our study for the dimethylsulfoxide solvent.…”
mentioning
confidence: 73%
“…(A) (B) Structure of PenAg by NMR spectroscopy with 500MHz LC-NMR instrumentation: An NMR study of PenNa has been previously reported [22,23]. Herein the binding mode of PenNa at PenAg is reported.…”
mentioning
confidence: 99%
“…Enhancement of antibiotic activity through complexation with metal ions is well ascertained. Copper (II), zinc (II) and silver (I) metal adducts with different antibiotics were extensively studied in recent years [ 242 , 243 , 244 , 245 ]. Cu(II) and Ag(I) themselves have antimicrobial activity [ 246 ], but together with antibiotics e.g., ampicillin, penicillin G and Cefuroxime, they present synergistic effects against Gram-positive (MRSA) bacteria ( S. aureus ).…”
Section: Enhancing Amps Activity With Metal Ionsmentioning
confidence: 99%
“…Cu(II) and Ag(I) themselves have antimicrobial activity [ 246 ], but together with antibiotics e.g., ampicillin, penicillin G and Cefuroxime, they present synergistic effects against Gram-positive (MRSA) bacteria ( S. aureus ). Zn(II) is an essential cofactor for metallo-β-lacamases (enzyme resistant to β-lactan antibiotics), and together with ampicillin and penicillin G shows a high synergistic effect [ 245 ].…”
Section: Enhancing Amps Activity With Metal Ionsmentioning
confidence: 99%
“…A resistência aos antibióticos é uma preocupação crescente na medicina e leva à necessidade de desenvolver e desenhar novas moléculas, potenciais fármacos, que possam inibir eficazmente a replicação bacteriana. Várias soluções têm sido tentadas, entre elas a síntese de complexos metálicos de alguns antibióticos já bastante utilizados clinicamente [Möhler et al, 2017;Cuprys et al, 2018].…”
Section: Introductionunclassified